Association of Sperm Methylation at LINE-1, Four Candidate Genes, and Nicotine/Alcohol Exposure With the Risk of Infertility - Zhang, Wenjing; Li, Min; Sun, Feng; Xu, Xuting; Zhang, Zhaofeng; Liu, Junwei; Sun, Xiaowei; Zhang, Aiping; Shen, Yupei; Xu, Jianhua; Miao, Maohua; Wu, Bin; et al. (Frontiers in Genetics, 2019)
In this study, we examined whether smoking and drinking affect sperm quality and the DNA methylation of the repetitive element LINE-1, MEST, P16, H19, and GNAS in sperm. Semen samples were obtained from 143 male residents in a minority-inhabited district of Guizhou province in southwest China. Quantitative DNA methylation analysis of the samples was performed using MassARRAY EpiTYPER assays. Sperm motility was significantly lower in both the nicotine-exposed (P = 0.0064) and the nicotine- and alcohol-exposed (P = 0.0008) groups. Follicle-stimulating hormone (FSH) levels were higher in the nicotine-exposed group (P = 0.0026). The repetitive element LINE-1 was hypermethylated in the three exposed groups, while P16 was hypomethylated in the alcohol and both the alcohol and nicotine exposure groups. Our results also show that alcohol and nicotine exposure altered sperm cell quality, which may be related to the methylation levels of MEST and GNAS. In addition, MEST, GNAS, and the repetitive element LINE1 methylation was significantly associated with the concentration of sperm as well as FSH and luteinizing hormone levels.